Implementasi Enkripsi Hybrid AES-RSA pada Layanan Cloud Storage AWS S3 - Firdaus, Mohamad Ricky; Hilabi, Shofa Shofiah; Novalia, Elfina; Hananto, April Lia (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Data security has become a critical aspect in the digital era, especially with the increasing use of cloud storage services for data storage and management. This study examines the implementation of hybrid encryption combining the Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA) algorithms on the Amazon Web Services Simple Storage Service (AWS S3) cloud platform. The hybrid method leverages the speed of AES for encrypting large data volumes and the security of RSA for key management. The encryption and decryption processes are performed entirely on the client side before uploading data to AWS S3, ensuring that the stored data remains securely encrypted. The developed application provides features for encryption, decryption, and uploading encrypted data with a user-friendly interface. Testing results demonstrate that this method achieves an optimal balance between performance and data security. This research contributes to the development of efficient and reliable cloud-based data security solutions.Keywords: Advanced Encryption Standard; Rivest–Shamir–Adleman; Amazon Web Services Simple Storage Service; Data Security; Cloud Storage AbstrakKeamanan data menjadi aspek penting dalam era digital, terutama dengan meningkatnya penggunaan layanan cloud storage untuk penyimpanan dan pengelolaan data. Penelitian ini mengkaji implementasi enkripsi hybrid yang menggabungkan algoritma Advanced Encryption Standard (AES) dan Rivest-Shamir-Adleman (RSA) pada layanan cloud storage Amazon Web Services Simple Storage Service (AWS S3). Metode hybrid ini memanfaatkan kecepatan AES dalam mengenkripsi data berukuran besar dan keamanan RSA dalam pengelolaan kunci enkripsi. Proses enkripsi dan dekripsi dilakukan sepenuhnya di sisi klien sebelum data diunggah ke AWS S3, sehingga memastikan data tersimpan dalam bentuk terenkripsi yang aman. Aplikasi yang dikembangkan menyediakan fitur enkripsi, dekripsi, dan upload data terenkripsi dengan antarmuka yang mudah digunakan. Hasil pengujian menunjukkan bahwa metode ini memberikan keseimbangan optimal antara performa dan keamanan data. Penelitian ini memberikan kontribusi dalam pengembangan solusi keamanan data berbasis cloud yang efisien dan dapat diandalkan.